Multiple sulfatase deficiency: A case series of four children - Incecik, Faruk (Medknow Publications & Media Pvt Ltd, 2013)
Multiple sulfatase deficiency is biochemically characterized by the accumulation of sulfated lipids and acid mucopolysaccharides. The gene sulfatase-modifying factor 1 (SUMF1), recently identified, encodes the enzyme responsible for post-translational modification of a cysteine residue, which is essential for the activity of sulfatases. We describe clinical findings and mutation analysis of four patients. The patients presented with hypotonia, developmental delay, coarse face, ichthyosis, and hepatosplenomegaly. The diagnosis was made through clinical findings, enzymatic assays, and mutation analysis. We were detected to be homozygous for a novel missense mutation c. 739G > C causing a p.G247R amino acid substitution in the SUMF1 protein.